Nutritional value of meat lipid fraction obtained from mallard duck (Anas platyrhynchos) reared in semiextensive conditions for hunting purposes - Quaresma, M. A. G. (2024)
Funding Information: The study received funding from FCT/MCTES through national funds. Therefore, there is no conflict of interest in this study. Funding Information: The authors thank to the company CAÇABRAVA (Santa Cita, Portugal), for providing the mallard duck specimens used in this study. The work was supported by FCT/MCTES through national funds, namely CIISA (UIDB/00276/2020) and AL4AnimalS (LA/P/0059/2020). The present manuscript is coauthored by researchers engaged with 5 different institutions belonging to the University and Research Centers. The present manuscript shows the reality of mallard duck being raised for hunting purposes by CAÇABRAVA. There is no direct or indirect link between the Researchers and CAÇABRAVA. The researchers have previously published other papers focusing on game meat quality. In those studies, as in this one, there is always the involvement of game producers or hunting farms, but sampling is permanently on the responsibility of the corresponding author. The study received funding from FCT/MCTES through national funds. Therefore, there is no conflict of interest in this study. Funding Information: The authors thank to the company CAÇABRAVA (Santa Cita, Portugal), for providing the mallard duck specimens used in this study. The work was supported by FCT/MCTES through national funds, namely CIISA ( UIDB/00276/2020 ) and AL4AnimalS ( LA/P/0059/2020 ). Publisher Copyright: © 2023 The Authors